Institutional Readiness and Faculty Awareness for Ethno-STEM and Augmented Reality Pedagogy: A Descriptive-Correlational Study in Masbate, Philippines - Mahawan, Alvin M.; Quiñones, John Rey B. (Future Science / FSH-PH Publications, 2026)
This descriptive–correlational study examined institutional readiness for integrating Augmented Reality (AR) in teaching and faculty awareness of Ethno-STEM pedagogy in a state college in Masbate Province, Philippines. Institutional readiness was assessed in terms of technological infrastructure, technical and administrative support, faculty digital competence, and organizational culture, while faculty awareness of Ethno-STEM was examined through conceptual understanding, perceived pedagogical value, and contextual application. Data were gathered from thirty-five (35) full-time faculty members using a validated survey instrument and analyzed using descriptive statistics and Pearson’s product–moment correlation through Jamovi. Results indicated that institutional readiness for AR integration (M = 3.02) and faculty awareness of Ethno-STEM pedagogy (M = 3.18) were both at a moderate level. While technological infrastructure and organizational culture were generally adequate, technical and administrative support emerged as a key area needing improvement. Faculty members demonstrated greater appreciation of the pedagogical value of Ethno-STEM than their capacity to apply it effectively in culturally contextualized instruction. Correlation analysis revealed that faculty digital competence (r = .482, p = .004) and organizational culture (r = .356, p = .041) were significantly associated with Ethno-STEM awareness, whereas technological infrastructure and technical support were not. These findings suggest that human and cultural dimensions of institutional readiness play a more decisive role than material resources in advancing culturally responsive, technology-enhanced pedagogy. The study provides empirical evidence to inform capacity-building initiatives that emphasize faculty professional development, supportive organizational cultures, and enabling institutional policies for effective AR and Ethno-STEM integration in teacher education.